COMPUTER-BASED CONVERGENCE OF LACTOSE MANUFACTURING TECHNOLOGICAL DECISIONS. TRADITIONAL WAY - Andrey Georgievich Khramtsov; Vladimir Alexandrovich Ermakov; Svetlana Andreevna Ryabtseva; Ivan Alekseevich Evdokimov; Georgy Sergeevich Anisimov; Dmitry Nikolaevich Lodygin (Вестник Северо-Кавказского федерального университета)
Peculiarities of lactose (milk sugar, produced by conventional technology) manufacturing process design usin step g Microsoft Project is considered. Cheese whey was applied as lactose-containing source raw material. Main s of Project «network graph scheduling - accounting of demanded sources and task performance term - Gantt diagram scheduling - project outcomes analysis)) are described. Completed work will be a source of further comparative analysis of different quality grade lactose technology.